Impact of medical imaging on the epigenome – low-dose exposure in the course of computed tomography does not induce detectable changes of DNA-methylation profiles in peripheral blood cells. (4th May 2022) - Becker, Benjamin Valentin; Kaatsch, Hanns Leonhard; Nestler, Kai; Jakobi, Julia; Schäfer, Barbara; Hantke, Thomas; Brockmann, Marc A.; Waldeck, Stephan; Port, Matthias; Ullmann, Reinhard
Abstract: Background: Computed tomography (CT) is a main contributor to artificial low-dose exposure. Understanding the biological effects induced by CT exposure and their dependency on the characteristics of photon spectra is essential for knowledge-driven risk assessment. In a previous gene expression study, we have identified upregulation of AEN, BAX, DDB2, EDA2R and FDXR after ex vivo exposure with single-energy CT and dual-energy CT (DECT). In this study, we focused on CT-induced changes of DNA methylation. This epigenetic modification of DNA is a central regulator of gene expression and instrumental in preserving genome integrity. Previous studies reported focal hypermethylation and global hypomethylation after exposure with doses above 100 mSv, however, the effect of low dose exposure on DNA methylation is hardly explored. Materials and methods: DNA was isolated from peripheral blood of three healthy individuals 6 h after ex vivo exposition to single-energy (80 kV and 150 kV) and DECT (80 kV/Sn150 kV) with a calculated effective dose of 7.0 ± 0.08 mSv. The experimental setting was identical to the one used in our previous gene expression study enabling a direct comparison of gene expression results with changes of DNA methylation identified in this study. DNA methylation was analyzed by high-throughput sequencing of bisulfite-treated DNA targeted methylation sequencing. Results: Unsupervised hierarchical clustering based on DNA methylation profiles of all samples created three distinct clusters. Formation of these three clusters was solely determined by the origin of samples, indicating the absence of prominent irradiation-associated changes of DNA methylation. In line with this observation, inter-individual comparison of non-irradiated samples revealed 1163, 1224 and 4550 significant differentially methylated regions (DMRs), respectively, whereas the pairwise comparison of irradiated and non-irradiated samples failed to identify irradiation-induced DMRs in any of the three probands. This even applied to the genomic regions harboring AEN, BAX, DDB2, EDA2R and FDXR, the five genes known to be upregulated by CT exposure. Conclusions: CT exposure with various photon spectra did not result in detectable changes of DNA methylation. However, minor effects in a subpopulation of irradiated cells cannot be ruled out. Thus, future studies with extended observation intervals are needed to investigate DNA methylation changes that are induced by indirect effects at later points of time or become detectable by clonal expansion of affected cells. Moreover, our data suggest that DNA methylation analysis is less sensitive in detecting immediate effects of low-dose irradiation when compared to gene expression analysis.